Physiological and biochemical parameters of winter wheat Triticum aestivum L. plants after seed treatment with fullerene C(60) - S. Prylutska; T. Tkachenko; M. Petrovsky (The Ukrainian Biochemical Journal)
Extreme climatic conditions, pests, diseases and environmental pollution significantly impact the cultivation of agricultural products and the quality of plant raw materials. It is assumed that nanostructured carbon materials, particularly fullerene C60, due to antioxidant, antiviral, and antibacterial properties can be used to prevent these effects. This study aimed to evaluate the effect of pre-sowing treatment of wheat seeds with fullerene C60 on the state of plants 14 days after germination. The seeds of the winter wheat Triticum aestivum L. of the Patras and Akter varieties were treated with a colloidal solution of fullerene C60 (0.1-1.0 µg/ml) for 3 h. Biomorphometric parameters, photosynthetic pigments, phenolic compounds, MDA content and catalase activity were assessed using standard techniques. It was shown that seeds treatment with fullerene C60 was followed by the greater increase of both the fresh weight of Akter plants and shoot length of Patras plants as compared to untreated controls. A dose-dependent effect of fullerene C60 on the physiological and biochemical parameters of the plants was revealed. Photosynthetic activity in plants of both wheat varieties was enhanced after seed treatment with C60 in low (0.1-0.2 µg/ml) concentrations as evidenced by the increased content of chlorophylls a, while at high (0.5-1.0 µg/ml) C60 concentrations it decreased against the background of increased carotenoids content. The enhancement of antioxidant defense induced by C60 treatment at concentrations of 0.5-1.0 µg/ml was observed, as indicated by an increase in the content of phenolic compounds and activation of catalase. The positive effect of wheat seeds treatment with fullerene C60 indicates the potential use of carbon nanoparticles in agrobiotechnologies to improve plant growth and stress resistance.